1997
DOI: 10.1177/095632029700800105
|View full text |Cite
|
Sign up to set email alerts
|

Distribution to the Brain and Protein Binding of 3′and 5-Substituted 2′,3′-Dideoxyuridine Derivatives, Studied by Microdialysis

Abstract: SummaryThe aim of this study was to investigate a series of 3' and 5-substituted 2',3' -dideoxyuridine derivatives (ddUD) with respect to plasma protein binding, halflife and distribution across the blood-brain barrier in the rat. The microdialysis technique was used to study protein binding in human plasma (in vitro), and to sample the extracellular space of rats with microdialysis probes implanted into the striatum of the brain and the gastrocnemic muscle (in vivo). The compounds were analysed by HPLC with U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This is in contrast to thymidine and 3 0 -azido-3 0 -deoxythymidine (AZT), which are less lipophilic and are far less protein bound (22 and 25%, respectively) [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to thymidine and 3 0 -azido-3 0 -deoxythymidine (AZT), which are less lipophilic and are far less protein bound (22 and 25%, respectively) [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots (50 ml) of these stock solutions were removed at specified time intervals (0.5, 1, 1.5, 2, 4,6,8,16,24,48,72,96, 120 h), and analyzed by quantitative HPLC. To determine stability in plasma, aliquots (10 ml) of a 1 mM solution of 5-IDFPdR in water were added to rat plasma (90 ml) to produce a 100 mM solution that was incubated at 378C in a water bath.…”
Section: -Idfpdrmentioning
confidence: 99%
“…We have recently demonstrated that chitosan-chloroquinoline conjugate has also potent antimicrobial activity [19]. Several previous studies have synthesized various thymine derivatives and reported potent anti-cancer effect [20][21][22][23]. More recently, Manna et al found that, modification of hyaluronic acid with thymine, by the LBL process, imparted them an anticancer activity [16].…”
Section: Introductionmentioning
confidence: 95%
“…But, to our best knowledge, Michael addition of pyrimidine with disaccharide acrylate catalyzed by lipase M from Mucor javanicus in organic medium has not been demonstrated. In this paper, we report a lipase M from Mucor javanicus-catalyzed Michael addition of sugarcontaining substrate for synthesis of pyrimidine derivatives containing a branched sugar which may possess potential antitumor and antivirus activities (Fedorov et al 1999, Borg et al 1997.…”
Section: Introductionmentioning
confidence: 99%